Profil Disolusi Terbanding, Penetapan Kadar, dan Kualitas Fisik Tablet Atorvastatin Inovator, Generik Bernama Dagang, dan Generik - Aini, Nurul; Saraswati, Ratih Dian; Oktoberia, Intan Sari (Jurnal Kefarmasian Indonesia, 2015)
Atorvastatin is one of the statins which is used as the first line therapy for hyperlipidemia. The patent of atorvastatin innovator ended in 2011. Besides the innovator brand of atorvastatin, several brand and one generic atorvastatin tablet are currently marketed in Indonesia. In this research, dissolution profiles, assay and physical quality were investigated for three atorvastatin tablet samples consist of one innovator sample, two atorvastatin copy layer products (branded generic atorvastatin sample and atorvastatin generic sample). The dissolution testing were done using FDA (Food and Drug Administration) method. The result shows that the innovator and branded generic samples meet all the requirements for physical quality, meanwhile the generic sample failed to meet the disintegration test criteria. The branded generic sample has similar dissolution profile with the innovator, while the generic tablet was not similar. The assay were conducted using High Performance Liquid Chromatography (HPLC) method. The assay result of the innovator, branded generic, and generic samples respectively were 97,54%, 106,36% and 97,65% which means that all samples comply with general requirement of active pharmaceutical ingredient in tablet.